Membaca Populisme Islam Model Baru - Garadian, Endi Aulia (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2017)
Vedi R. Hadiz, Islamic Populism in Indonesia and the Middle East. Cambridge: Cambridge University Press. x + 228pp.This book wants to illustrate the compatibility of democracy with Islam. Under certain circumstances, it could be happened when alliances of marginalized classes unite in one shade under the banner of Islam. Focussing on Muslims in Indonesia, Egypt, and Turkey, Vedi R. Hadiz tries to see the process of Islamic populism formulation. This book elaborates more deeply the relationship between democratization, socio-economic change and the unbearable desire of globalization that has an impact on the evolution of the Muslim community’s struggle on those countries. By emphasizing the economic-political and socio-historical perspectives, the important point to be conveyed by Vedi that the motivation of the group interests and the economic advantages, to some extent, can give birth to the political power of Islam in the midst of society, rather than the ideology and the teachings of religion itself. Hence, basically, there is nothing that distinguishes Islamic political phenomena from the general political phenomenon. Finally, this book is important to read by those who want to get the latest framework in explaining the current development of Islamic Populism.DOI: 10.15408/sdi.v24i2.5708